Answers

2015-09-14T23:20:21+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
In the right angle triangle ABD, we have
         AD² = AB² - BD²
In the right angle triangle  ACD we have
        AD² = AC² - CD²

So    AC² - CD²  = AB² - BD²
        =>  AC² = AB² + CD²  -  BD²
        =>         = AB² + (CD + BD)* (CD - BD )
                     = AB² + BC * [(BC - BD) - BD]
                     = AB² + BC * [ BC - 2 BD ]
                       = AB² +BC² - 2 BC * BD

1 5 1
click on thanks button above please
select best answer pls